KAJIAN ANALISIS HADIS TENTANG TOLERANSI PADA BUKU TEKS PENDIDIKAN AGAMA ISLAM SMA KELAS X - ruhmina; Romlah Abubakar Askar (Fakultas Agama Islam Universitas Islam Jakarta, 2025)
Tolerance is an essential principle in Islamic teachings that emphasizes respect for differences and harmonious social life. This value is reflected in various verses of the Qur'an and hadiths, which highlight the importance of justice, religious freedom, and openness to human diversity. This study aims to analyze the function of hadiths in the discussion of tolerance material in Islamic Religious Education (PAI) textbooks for senior high school (SMA) grade X. The research employs a qualitative approach through a library study method with descriptive-analytical techniques. Data were obtained from PAI textbooks and relevant literature on hadith and the interpretation of tolerance-related verses. The findings indicate that hadiths in these textbooks primarily serve as supportive or complementary sources that reinforce the message of tolerance in Islamic teachings. Islam teaches tolerance in a systematic manner, starting with conscious belief selection, followed by an understanding of religious diversity, and ultimately fostering the ability to maintain good social relations without compromising the core principles of faith. The incorporation of tolerance values in Islamic education is expected to shape students into inclusive individuals, socially wise, and firm in their religious beliefs. Keywords: tolerance, hadith, Islamic Religious Education, PAI high school textbook